Intention to Care for COVID-19 Patients Among Nurses Working at Health Care Institutions of Debre Tabor Town, North Central Ethiopia - Minuye B; Alebachew W; Kebede M; Asnakew S; Mesfin Belay D (Dove Medical Press, 2021)
Binyam Minuye, Wubet Alebachew, Melese Kebede, Sintayehu Asnakew, Demeke Mesfin Belay College of Health Sciences, Debre Tabor University, Debre Tabor, EthiopiaCorrespondence: Binyam Minuye Tel +251921574025Email biniamminuye@yahoo.comBackground: Coronavirus disease 2019 (COVID-19) has caused many challenges for health care providers. Nurses meet patients with coronavirus disease and offer care for newly communicable diseases. Despite global and national efforts to prevent the spread, the outbreak is still on a rise, and studies on the health care behaviors of nurses were scarce in the study setting. Therefore, this study was intended in addressing nurses’ intention to care for coronavirus disease 19 patients and its determinants among nurses working at Debre Tabor town Health Care Institutions, 2020.Methodology: An institutional-based cross-sectional study was conducted among 163 nurses working at health care institutions of Debre Tabor Town, from June 01 to 15/2020. The data were collected using tools with a self-administration questionnaire adapted from the theory of planned behavior and different kinds of literatures. All nurses working at Debre Tabor health care institutions were included. Data were entered using Epi-data 4.2.0.0 statistical software, and analysis was done by Stata version 14 statistical software. Binary logistic regression model was used for analysis. Strength of association was measured using the odds ratio with 95% CI, and the level of significance was estimated at P-value ≤ 0.05.Results: Nurses’ intention to care for COVID-19 patient was 59.5% (95% CI; 58.7:60.3). Having better working experience (adjusted odds ratio (AOR) =2.3:95% CI; 1.120, 4.910), caring experience for infectious disease (AOR=2.5; 95% CI: 1.10, 5.50), good perceived behavioral control (AOR=2.33; 95% CI: 1.13, 4.8), and subjective norms (AOR= 2.14; 95% CI: 1.05, 4.36) were significantly associated with intention of caring behavior.Conclusion: Nurses’ intention to care for COVID-19 patients was low. Working experience, the experience of caring for infectious disease, self-efficacy, and subjective norm were independently related with nurses’ caring intention. The government should work on improving nurse’s confidence in disaster management, design disaster management nursing education, and frequent support of nurses.Keywords: theory of planned behavior, coronavirus, nurse, intention to care, Ethiopia